Cataract Formation in a Child Receiving Dabrafenib and Trametinib Therapy - Botros, Elaine; Bradfield, Yasmin; Pytel, Nicholas (Journal of pediatric ophthalmology and strabismus, 2024)
The authors report a case of bilateral cataract in a 9-year-old girl after being treated with a combination of the targeted therapy drugs dabrafenib and trametinib. Although adverse effects have been reported with this treatment, this report is the first documented case of cataract as a complication. [J Pediatr Ophthalmol Strabismus. 2024;61(5):e47–e49.]